2006
DOI: 10.4018/jgim.2006010102
|View full text |Cite
|
Sign up to set email alerts
|

E-Government Strategies in Developed and Developing Countries

Abstract: Given the fact that more and more governments invest heavily in e-government design and implementation, e-government has become an evolving and important research area in the IS field. Most, if not all, currently published e-government strategies are based on successful experiences from developed countries, which may not be directly applicable to developing countries. Based on a literature review, this study summarizes differences between developed/developing countries. It identifies key factors for a successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
0
34

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(154 citation statements)
references
References 20 publications
1
95
0
34
Order By: Relevance
“…Tregear andJenkins, 2007 &Fettke et al, 2014) Chen, Chen, Huang, and Ching (2006) stated that national e-Government infrastructure, culture, and society factors are different between developed and developing countries and strongly argued that developing countries should design their own e-Government strategies based on their unique factors instead of adopting the strategies of the developed countries. Apart from restrictions on the technological infrastructure and financial capabilities needed for e-Government, developing countries are constrained with competencies and know-how to develop robust strategies for developing and supporting Government improvement initiatives (Chen et al, 2006). Bin Taher, Krotov, and Silva (2015) argued that the models and experience of developed countries cannot be directly applied in developing countries due to various socio-economic and cultural differences.…”
Section: Public Sector Private Sector Culturementioning
confidence: 99%
“…Tregear andJenkins, 2007 &Fettke et al, 2014) Chen, Chen, Huang, and Ching (2006) stated that national e-Government infrastructure, culture, and society factors are different between developed and developing countries and strongly argued that developing countries should design their own e-Government strategies based on their unique factors instead of adopting the strategies of the developed countries. Apart from restrictions on the technological infrastructure and financial capabilities needed for e-Government, developing countries are constrained with competencies and know-how to develop robust strategies for developing and supporting Government improvement initiatives (Chen et al, 2006). Bin Taher, Krotov, and Silva (2015) argued that the models and experience of developed countries cannot be directly applied in developing countries due to various socio-economic and cultural differences.…”
Section: Public Sector Private Sector Culturementioning
confidence: 99%
“…Clarke (2000), Chen et al (2006), and Chaffey (2007) identified a number of barriers to ebusiness adoption such as: lack of established theories, instability of phenomena, variations in culture, low-level investments in IT, lack of resources and skilled workforce, and limited growth strategies. The adoption of Internet technologies and e-business by SMEs has been slower in comparison to large companies worldwide (Marshall et al, 2000).…”
Section: Barriers In Adoption Of Internet and E-businessmentioning
confidence: 99%
“…Another big challenge in eGovernment implementation is human resources, where developed countries had many qualified HR or expert staff who able to define requirements or needs in e-Government system. Further, the one is also lack of well-skilled and trained people that could bring the initiative of e-Government implementation [11] [12]. According to Heeks (2008), level of failure implementation of e-Government was quite high until 85%, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%